2008
DOI: 10.1088/0268-1242/23/8/085008
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of nitrogen-doped p-ZnO thin films and ZnO/ZnSe p–n heterojunctions grown on a ZnSe substrate

Abstract: We investigate p-type doping in ZnO prepared by the method of radical beam gettering epitaxy using NO gas as the oxygen source and nitrogen dopant. A narrow (0 0 2) peak is observed in the x-ray diffraction spectra, which indicates that the N-doped ZnO films are oriented along the c-axis. Secondary ion mass spectroscopy measurements demonstrate that N is incorporated into a ZnO film with a concentration of about 2.5 × 10 19 cm −3 . The hole concentration of the N-doped p-ZnO films was between 1.4 × 10 17 and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…Also, the emission lines in this spectral region are typically attributed to native defects. 12 The peaks related to nitrogen doping at $3.31-3.315 eV (acceptor bound exciton), 12,14 and 3.24 eV donoracceptor pair (DAP) emission 14 could not be clearly resolved, although from the shape of the peak contributions in this spectral region cannot be excluded.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the emission lines in this spectral region are typically attributed to native defects. 12 The peaks related to nitrogen doping at $3.31-3.315 eV (acceptor bound exciton), 12,14 and 3.24 eV donoracceptor pair (DAP) emission 14 could not be clearly resolved, although from the shape of the peak contributions in this spectral region cannot be excluded.…”
Section: Resultsmentioning
confidence: 99%
“…1,3,4 Among different possible acceptor dopants for ZnO, nitrogen has been regarded as one of the most suitable acceptors due to its similar atomic size and electronic structure to oxygen, 3 and hence, it has been extensively studied. [5][6][7][8][9][10][11][12][13][14][15][16] However, p-type conductivity in N:ZnO remains controversial. 3,4 Recent theoretical calculations indicated that nitrogen is a deep acceptor, 5 although hole binding energy derived from PL experiments on N:ZnO was comparable to that observed for Mg in GaN, 4 indicating that nitrogen is a shallow acceptor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This transition could be due to donor-acceptor pair (DAP) recombination, which involves the same acceptor as the (FA) transition at 3.314 eV. Transitions at ∼3.24 eV and ∼3.17 eV have been reported in ZnO doped with nitrogen [9,10]. Rogozin et al [9] reported a DAP emission at 3.24 eV in their p-type ZnO grown with NO.…”
Section: Introductionmentioning
confidence: 97%
“…To overcome this drawback a number of technologies can be used (MBE, metal organic chemical vapor deposition (MOCVD), ion implantation), but all of them need complex and expensive facilities and a suppression of radiation defects by additional annealing. Recently, a new method has been proposed, which is the ZnO:N thin films deposition using the radical-beam generating epitaxy method for p-ZnO/ n-ZnSe anisotropic heterojuction formation [2]. In this work we report on the photothermal oxidation method applied to the mentioned heterojunction fabrication and the studies of its electric properties.…”
Section: Introductionmentioning
confidence: 99%